A duplex fluorescent quantitative PCR assay to distinguish the genotype I and II strains of African swine fever virus in Chinese epidemic strains - Cao, Shinuo; Lu, Huipeng; Wu, Zhi; Zhu, Shanyuan (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a highly contagious hemorrhagic disease that affects domestic and wild pigs. A recent study reported that both ASF virus (ASFV) genotypes I and II have invaded farm-raised pigs in China, causing chronic infection and morbidity. To develop a duplex fluorescent quantitative PCR method to distinguish the ASFV genotypes I and II in Chinese epidemic strains, the probes and primers were designed based on the B646L sequences of genotypes I and II listed in the GenBank database. After optimizing the system, a duplex fluorescent quantitative PCR method for simultaneous detection of ASFV genotypes I and II B646L genes was successfully established. This method had no cross-reaction with Porcine circovirus type 2 (PCV2), Pseudorabies virus (PRV), or Porcine Parvovirus (PPV), indicating that it has strong specificity. The sensitivity results indicated that the minimum detection limit of ASFV genotypes I and II B646L was 10 copies/Rxn. The inter- and intra-group coefficients of variation were both <3%, indicating that the method was highly reproducible. Therefore, the established duplex fluorescent quantitative PCR assay is important for the differential detection and epidemiological investigation of ASFV.